Cognitive Impairment and Memory Loss in Diabetes: A Myth or Reality - Malik, Madeeha; Bi, Sidra; Hussain, Azhar (Journal of Pharmacy Practice and Community Medicine)
Diabetes itself might not be a risk factor but mismanagement and poor control of disease may lead to the problem. High blood glucose levels, elevated blood pressure, obesity and high cholesterol collectively lead to complications including decline in cognitive ability. The present study was designed to explore the factors effecting cognitive impairment and memory loss among diabetes patients in twin cities of Pakistan. A descriptive cross-sectional study design was used. A pre-validated data collection tool i.e. Mini Mental State Examination (MMSE) questionnaire, which is a practical method for grading the cognitive state of patients was distributed to a sample of 386 diabetes patients. After data collection the data was cleaned, coded and statistically analyzed using SPSS version 21. Out of 386 respondents 97.75% (n=377) had normal cognition level, 2.3% (n=9) had mild decline in cognition level while none of the respondents had moderate or severe cognitive impairment. Significant association for cognitive impairment and demographic variables such as gender (p = 0.006) was observed. However, no significant association for cognitive impairment was observed for age, qualification, duration and type of disease, class of medication, income level, control of disease and medication adherence. The present study concluded that majority of the diabetes patients did not show cognitive impairment and memory loss. However, mild cognitive decline was observed among males, elderly and more common in type II diabetes patients. Better qualification and income can improve knowledge, adherence and disease appraisal resulting in better approach towards management of disease. This in turn can positively affect cognition and memory loss. Thus, it can be assumed that diabetes might not directly play major role in cognitive impairment and memory loss but its poor management may affect psychomotor functions of the patients.
Keywords: Cognitive impairment; Memory loss; Diabetes; Pakistan